Solution;
Rewrtie the equation as follows:
"\\frac{dy}{dx}" +P(x)y=Q(x)yn
"\\frac{2y^3-x^3}{3x^2y}+\\frac{dy}{dx}=0"
"\\frac{dy}{dx}-\\frac{x}{3y}=-\\frac{2}{3x^2}y^2"
The equation is not a Bernoulli's so we solve as an homogenous equation.
"\\frac{dy}{dx}" =-"\\frac{2y^3-x^3}{3x^2y}"
Take
y=Vx
"\\frac{dy}{dx}" =v+x"\\frac{dv}{dx}"
v+x"\\frac{dv}{dx}" =-"\\frac{2v^3x^3-x3}{3vx^3}"
Divide the R.H.S with x3
v+x"\\frac{dv}{dx}" ="\\frac{1-2v^3}{3v}"
Separate the variables;
"\\frac{3v}{1-2v^3-3v^2}"dv="\\frac1x" dx
Integrating both sides;
3("-\\frac{ln(2v-1)}{9}" +"\\frac{ln(v+1)}{9}"+"\\frac{3}{3v+3}" =ln(x)+C
But v="\\frac yx"
-"\\frac{ln(\\frac yx-1)}{3}" +"\\frac{ln(\\frac yx+1)}{3}"+"\\frac{3}{3\\frac yx+3}" =ln(x)+C
Comments
Leave a comment